2012
DOI: 10.1039/c2cy00413e
|View full text |Cite
|
Sign up to set email alerts
|

A DRIFTS study of CO adsorption and hydrogenation on Cu-based core–shell nanoparticles

Abstract: Core-shell nanoparticles are being considered for various applications due to their controllable atomic structure and improved properties compared to their bulk counterparts. In the present work, we have synthesized Cu@Mn 3 O 4 and Cu@Co 3 O 4 (core@shell) nanocatalysts using wet-chemical synthesis methods involving organic surfactants, and probed their surfaces using CO and H 2 under reaction conditions using diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The surfactant ligands used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 62 publications
0
39
0
Order By: Relevance
“…A DRIFTS reactor is particularly suited to this 7 type of investigation since the catalyst powder can be used directly as such and therefore 8 DRIFTS is becoming a major technique for catalytic applications at the gas-solid interface. 9 Some commercial DRIFTS cells enable using high reaction temperatures and high pressures 10 [19,20], whereas it is more difficult to built IR cell in transmission mode respecting these 11 experimental conditions [21]. 12 DRIFTS exhibits a higher sensitivity with respect to surface species and strongly 13 absorbing samples such as carbon-based materials can be studied [22].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…A DRIFTS reactor is particularly suited to this 7 type of investigation since the catalyst powder can be used directly as such and therefore 8 DRIFTS is becoming a major technique for catalytic applications at the gas-solid interface. 9 Some commercial DRIFTS cells enable using high reaction temperatures and high pressures 10 [19,20], whereas it is more difficult to built IR cell in transmission mode respecting these 11 experimental conditions [21]. 12 DRIFTS exhibits a higher sensitivity with respect to surface species and strongly 13 absorbing samples such as carbon-based materials can be studied [22].…”
Section: Introductionmentioning
confidence: 98%
“…16 In particular, DRIFTS analyses were able to show that the heat of CO adsorption on a Pt-Sn 17 alloy was about half the value measured on plain Pt, and that Pt-Sn segregation took place 18 reversibly in the presence of CO when the temperature was lower than 175°C [27]. DRIFTS 19 could also be used to investigate mass transport properties of zeolites, using sample masses 20 lower than 1 mg [28]. 21 This increased popularity is also due to the availability of a number of affordable 22 commercial cells, though those may exhibit hydrodynamic flaws [29,30] or important 23 temperature gradients that may need to be taken into account [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) is a powerful surface-sensitive technique to peer into the adsorption behavior of catalysts under reaction conditions. 19 Moreover, it is helpful to clarify the relation between the adsorption and reaction via probe molecule such as CO. 20 However, it was barely reported that DRIFTS was employed to characterize the Cu-Co based catalysts modified by rhodium to date. In this work, the CuCo/γ-Al 2 O 3 catalysts modified by rhodium were prepared and their CO hydrogenation activities were evaluated.…”
Section: Introductionmentioning
confidence: 99%